A preliminary study of subsymptom threshold exercise training for refractory post-concussion syndrome - Leddy, J. J.; Kozlowski, K.; Donnelly, J. P.; Pendergast, D. R.; Epstein, L. H.; Willer, B. (Clinical Journal of Sport Medicine, 2010)
The article presents a study on the effectivity of subsymptom threshold exercise training (SSTET) as a treatment for post-concussion syndrome (PCS). It mentions that refractory patients participated in the study including six athletes and nonathletes with PCS. It states that the participants performed a treadmill exercise test which was ended when exacerbation of PCS symptoms were reported. Moreover, the controlled exercise seems to be a safe program for PCS treatment to ameliorate PCS symptoms.